POVERTY ALLEVIATION IN INDONESIA DURING THE COVID-19 PERIOD 2019-2022: SYSTEMATIC LITERATURE REVIEW WITH VOS VIEWERS BIBLIOMETRICS - Dina Arfianti Siregar; Zuhrinal M Nawawi; Isnaini Harahap (SEAN Institute, 2023)
Poverty is a multidimensional problem because it is related to the inability to access economically, socio-culturally, politically and participate in society. The forms of poverty that exist in Indonesia and the various factors that cause them, of course, greatly influence the policy formulation that is made. This research was conducted by analyzing 20 of the 420 articles searched through the Publish or Perish application from 2019-2022 from selected literature discussing poverty using the publication name